The rediscovery of two files relating to the Karakoram (1928–1929) and North Pole (1928) expeditions conserved at the Municipal Archives in Milan - Stefano Andrea Twardzik (Routledge, 2022)
The Milan Municipal Archives, today “Citadel of Archives”, conserves bulky files related to a couple of Italian geographical expeditions whose results differed considerably: the 1928-1929 Karakorum expedition led by Prince Aimone of Savoia-Aosta, and the 1928 North Pole expedition led by General Umberto Nobile. The nine huge bundles into which the two dossiers are divided, illustrate various aspects of the events, above all their organizational, finance, publishing rights management and legal dispute implications. Both planned in 1927, these expeditions were forcefully supported by the Municipality of Milan through a subscription raised with banks, industry and insurance companies, who accumulated a huge endowment fund to cover the estimated costs of the two expeditions. The presidency of the funding committee became the heart of the financial and organizational phases in both enterprises and since the role of president of the committee was entrusted to the podestà of Milan (the present major), the two files were managed directly by the leadership of the Municipality, with the bureaucratic support of the podestà’s special secretariat: this explains the presence of these papers at the municipal records office, where they were transferred in 1935. This contribution supplies a first summary inventory of the dossiers, so far essentially unknown, and focuses on the more significant issues that emerge from the records: the harsh contrast between General Nobile and the Milanese Committee and the rich photographic documentation that has been found inside the Karakorum file.